2015
DOI: 10.1186/s40200-015-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Norouz holiday on anthropometric measures and body composition

Abstract: BackgroundThis study examined the effect of holiday season on the anthropometric measures in Shariati hospital staff.MethodsThis study was conducted in 2014 on 66 subjects, aged 21–68 years. Weight, height, waist circumference (WC), hip circumference (HC), waist -to-hip ratio (WHR), waist-to- height ratio (WHtR) and physical activity were measured. Bioelectrical impedance analysis (BIA) method and the Tanita body composition analyzer were used to analyze body composition.ResultsIn this study, 80.3% of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Significant increase in trunk fat mass of the participants during holiday in this study is in line with the findings of Costa et al and Hull et al [7,8]. In contrast, Wagner et al found no significant difference in fat percent [17], while Payab et al [23] observed a significant decrease in fat percent, as well as a significant increase in fat free mass among the hospital staff during Nowruz holiday.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Significant increase in trunk fat mass of the participants during holiday in this study is in line with the findings of Costa et al and Hull et al [7,8]. In contrast, Wagner et al found no significant difference in fat percent [17], while Payab et al [23] observed a significant decrease in fat percent, as well as a significant increase in fat free mass among the hospital staff during Nowruz holiday.…”
Section: Discussionsupporting
confidence: 91%
“…We observed increased in adiposity during holiday are in line with the findings of Cooper et al [13], Montero et al [11], Yanovski et al [19], Costa et al [7] and Branscum et al [22]. Similarly, Payab et al recently reported significant weight gain during Nowruz holiday among the staff of a hospital in Tehran, Iran [23]. Cooper et al conducted a prospective study to determine if a 1-to 3-week vacation in adults leads to weight gain and whether that gain persists 6 weeks later.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed an increase of 1.5 to 1.7 kg ( p < 0.001) in men and women, respectively [ 34 ]. Payab et al ascertained the effects of the Persian New Year Festival “Norouz,” which takes place at the beginning of spring [ 36 ]. Sixty-six subjects, aged 21–68 years participated in anthropometric measurements in mid-March and April (approximately 45 days apart).…”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with increased caloric intake and low energy expenditure, causing an imbalance resulting in weight gain. In the United States, an average weight gain of 3.6 kg is reported during holidays (Yanovski et al, 2000;Payab et al, 2015). It has also been reported that the risk of weight gain is higher for obese people (Stevenson et al).…”
Section: Introductionmentioning
confidence: 99%